THE EFFECT OF TEACHING METHODS AND LEARNING MOTIVATIONS ON STUDENTS’ SPEAKING SKILL - Acep Bahrum Kamil (Universitas Singaperbangsa Karawang, 2017)
This research is aimed at findings out the 1) difference between discussion and role play method in affecting students’ speaking skill; 2) interaction of teaching methods and learning motivation on students’ speaking skill; 3) if role play is more effective for the students with high learning motivation than discussion on students’ speaking skill; 4) if discussion is more effective for the students with low learning motivation than role play on students’ speaking skill. This research was factorial design where the class was divided into two classes and four groups. The total of sample of each group is 20 students. So the total of sample is 80 students. This research was conducted eight time meetings. The instruments of this research are learning motivation questionnaire and test. The result of the research shows that, there was no interaction between learning motivation and teaching method. This result supported by the result of two ways a nova Fobserved 2.98 < Ftable 3.97, but the implementation of group discussion method is effective to improve the speaking skill with students who are high motivation than students who are low motivation. The difference is based on the level of students’ motivation. Thus, it can be concluded that for the students with high motivation, discussion is more effective than role-play on students’ speaking skill. Therefore, role-play is more effective than discussion on students’ speaking skill for students who have low learning motivation at the eleventh grade of SMAN 1 Pangkalan Karawang. Keywords: Role play, Discussion, learning motivation, speaking skill